Assessment of ilness perception of diabetic patients with periodontitis - Abdullah, Basiroh; Che Shari, Nurul Fadzlin; Faisal, Ghasak Ghazi; Al-Ani, Ali Sabri Radeef; Mohamed Ali, Suhaila (Ektodermal Displazi Grubu - Türkiye, 2017)
Illness perception is the organized cognitive representations or beliefs that patients have about their illness. These perceptions are important determinants of behavior and are associated with important illness outcomes. This study aimed to assess the illness perception of diabetic patients with periodontitis toward Diabetes Mellitus and periodontitis and its association with the severity of periodontitis. A cross sectional prospective study was conducted among total of 22 diabetic patients with periodontitis attending the periodontics Kulliyyah of Dentistry (KOD) Polyclinic, International Islamic University Malaysia (IIUM). Periodontal clinical examination was done to the patients and the severity of periodontitis was determined by the clinical attachment loss (CAL).The Brief Illness Perception Questionnaire (B-IPQ) was used to assess illness perception towards Diabetes and periodontitis. The mean score of illness perception in diabetes mellitus is higher than periodontitis in terms of timeline, personal control, concern, and understanding. The patients that perceive the illness in a serious way in terms of consequences, treatment control, concern, and emotional domain have lower mean CAL. There is significant relationship between gender and illness perception towards Diabetes Mellitus and periodontitis for identity domain where male patients showed p value of 0.04 and 0.032 respectively. This study showed that patients consider Diabetes Mellitus to be more serious than periodontitis despite the severity of their periodontitis. This highlights the intense need of proper education about the oral complications of Diabetes Mellitus and oral health in general.